Anti-cancer study and whey protein complexation of new lanthanum(III) complex with the aim of achieving bioactive anticancer metal-based drugs. Issue 8 (24th May 2019) - Shahraki, Somaye; Shiri, Fereshteh; Heidari Majd, Mostafa; Dahmardeh, Somaye
Abstract: In this study, a new lanthanum (III)-amino acid complex utilizing cysteine has been synthesized and characterized. The anticancer activities of the prepared La(III) complex against MCF-7 cell lines were studied. Results of MTT assay showed that at all three incubation times, the cytotoxic effect of prepared La(III) complex on MCF-7 breast cancer cell lines displays a time- and dose-dependent inhibitory effects. The interactions of the La(III) complex with two whey proteins (bovine serum albumin, BSA, and Bovine β-lactoglobulin, βLG) have been explored by using spectroscopic and molecular dicking methods. The obtained results indicated that La(III) complex strongly quenched the fluorescence of two carrier proteins in static quenching mode and also, BSA hah stronger binding affinity toward studied complex than βLG whit binding constant values of K BSA-La Complex  ∼ 0.11 × 10 4 M −1 and K βLG-La Complex  ∼ 0.63 × 10 3 M −1 at 300 K. The thermodynamic parameters revealed the contribution of hydrogen bond and Vander Waals interactions in both systems. The distances of the La(III) complex whit whey proteins were calculated using Förster energy transfer theory and proved existence of the energy transfer between two proteins and prepared La(III) complex with a high probability. FT-IR and UV–Vis absorption measurements indicated that the binding of the La(III) to BSA and βLG may induce conformational and micro-environmental changes of the proteins. The docking results indicate that the La(III) complex bind to residues located in the site II of BSA and second site of βLG. Communicated by Ramaswamy H. Sarma